Local Fiscal Effects of Immigration in Germany - Simone Maxand; Hend Sallam (CESifo GmbH, 2024)
We investigate the impact of immigration on public budgets using administrative data from German districts (Kreise). While previous literature suggests that the fiscal benefits of migration depend on government spending responses to immigration, the local-level effects in Germany remain relatively unexplored. Our study analyzes how immigration influences public spending, the provision of public goods, and public revenues from 2010 to 2019. Employing the post-double selection LASSO method for model identification and instrument generation, our results suggest that an increase in the foreign population proportion at the district level does not significantly affect public investment spending or collected tax revenues. Overall, along with 2011 results at the community level (Gemeinde), this research discusses the importance of distinguishing between different local levels, migration groups, and expenditure categories, when studying the gains and burdens of immigration in Germany.
Keywords: H53; I38; H70; H72; 330; immigration; size of the government; welfare state; local budgets; spatial economy; public revenues; public spending